1989
DOI: 10.1097/00004032-198908000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Technetium Absorption and Turnover in Monogastric and Polygastric Animals

Abstract: Technetium (Tc) released into the environment can reach animals in various chemical forms: as pertechnetate (TcO-4) in drinking water or deposited on the surface of vegetables and forage plants, or as Tc bioincorporated into plants and associated with various plant constituents. In addition to being influenced by chemical speciation in the diet, absorption, metabolism, and retention of Tc in animals are modified by the treatment that the alimentary bolus undergoes during its passage through the gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…We obtained transfer factors of 0.05 for kidneys, and 0.07 for the liver. This result is close to those to Gerber et al [6] and Jones [1] from which we calculated respective transfer factors of 0.07 and 0.05 for the kidneys, and 0.08 and 0.03 for the liver. On the other hand, if we are interested in tissues where the balance is not reached, we can give as indication a "temporary" transfer factor of 4.27 for the thyroid and 3.38 for the…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We obtained transfer factors of 0.05 for kidneys, and 0.07 for the liver. This result is close to those to Gerber et al [6] and Jones [1] from which we calculated respective transfer factors of 0.07 and 0.05 for the kidneys, and 0.08 and 0.03 for the liver. On the other hand, if we are interested in tissues where the balance is not reached, we can give as indication a "temporary" transfer factor of 4.27 for the thyroid and 3.38 for the…”
Section: Discussionsupporting
confidence: 92%
“…The single exposure underestimates the real uptake of Tc by these tissues. Indeed, Gerber et al [6] obtains transfer factors of only 1.4 and 0.1 for the thyroid and the hair, respectively.…”
mentioning
confidence: 99%
“…The second estimate of leaching was performed by measuring activity in urine [14,15] from the subjects sampled during the first 24 h after exposure. classifier model 3071, condensation particle counter (CPC) models 3010 and 3020).…”
Section: Methodsmentioning
confidence: 99%
“…Presence of oxygen during particle generation produces pertechnetate ( 99m TcO 4-), which instantaneously leaches off the labelled particles in body fluids [17][18][19]. Pertechnetate assembles in the thyroid and is excreted with urine within days [14,15]. This may contribute to the results interpreted as translocation in the study by NEMMAR et al [11], in which thyroid glands and bladder were visible in the whole body scan.…”
Section: Negligible Clearance Of Ultrafine Particles P Wiebert Et Almentioning
confidence: 99%
“…Here we analyse interspecies differences in 99 Tc transfer from soil-to-plants to aid assessments of 99 Tc behaviour in the environment. Technetium-99 released into soils has the potential to contaminate food chains, although its radiological effects are normally only considered to be significant at very high activities (Gerber et al, 1989). In a review of data generated prior to 1983, Coughtrey et al (1983) concluded that transfer of 99 Tc from soil-to-plant was affected by soil factors, and by intra-species and inter-species effects.…”
Section: Introductionmentioning
confidence: 99%